2016
DOI: 10.1093/nar/gkw606
|View full text |Cite
|
Sign up to set email alerts
|

HOXA1 binds RBCK1/HOIL-1 and TRAF2 and modulates the TNF/NF-κB pathway in a transcription-independent manner

Abstract: HOX proteins define a family of key transcription factors regulating animal embryogenesis. HOX genes have also been linked to oncogenesis and HOXA1 has been described to be active in several cancers, including breast cancer. Through a proteome-wide interaction screening, we previously identified the TNFR-associated proteins RBCK1/HOIL-1 and TRAF2 as HOXA1 interactors suggesting that HOXA1 is functionally linked to the TNF/NF-κB signaling pathway. Here, we reveal a strong positive correlation between expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 68 publications
(107 reference statements)
2
66
0
Order By: Relevance
“…Loss-of-function and lineage studies have implicated Hoxa1 in development of the inner ear, heart, neural crest specification, and hindbrain patterning (31)(32)(33). Growing evidence suggests roles for Hoxa1 in etiology of various cancers through modulation of cell proliferation, invasion, and metastasis (34)(35)(36)(37). These diverse functional roles for Hoxa1 appear to be at least partially related to its ability to influence key signaling pathways in differentiating cells (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function and lineage studies have implicated Hoxa1 in development of the inner ear, heart, neural crest specification, and hindbrain patterning (31)(32)(33). Growing evidence suggests roles for Hoxa1 in etiology of various cancers through modulation of cell proliferation, invasion, and metastasis (34)(35)(36)(37). These diverse functional roles for Hoxa1 appear to be at least partially related to its ability to influence key signaling pathways in differentiating cells (35).…”
mentioning
confidence: 99%
“…Growing evidence suggests roles for Hoxa1 in etiology of various cancers through modulation of cell proliferation, invasion, and metastasis (34)(35)(36)(37). These diverse functional roles for Hoxa1 appear to be at least partially related to its ability to influence key signaling pathways in differentiating cells (35).…”
mentioning
confidence: 99%
“…Analysis was also made of HOXA1 expression and an upregulated expression was observed by the high protein diet. Overexpression of HOXA1 is shown to cause an increased inflammatory response by interacting with signal transducers involved in the TNF/NF‐κB pathway, thereby causing increased secretion of pro‐inflammatory biomarkers including TNFα and IL‐8 . In addition, the differentially expressed miRNAs (miR‐99a‐5p and miR‐100 ‐5p) identified in this study have been reported to directly target HOXA1 in various cancers and their expression is reported to be inversely correlated with HOXA1 gene expression .…”
Section: Discussionmentioning
confidence: 66%
“…The plasmids pML‐ EphA2 ‐r4‐Luc , pML‐ Hoxb1‐ARE ‐Luc , pCMV‐ Lacz , the pEXP‐FLAG(Nter)‐ Hoxa2 , pCMV‐ Pbx1 , pCS2‐ Prep1 , pEXP‐FLAG(Nter)‐ Hoxa1 , pEXP‐GST(Nter)‐ Hoxa1 , pEXP‐VC155(Nter)‐ Hoxa1 , pEXP‐FLAG(Nter)‐ Hoxa1 ΔNter , pEXP‐FLAG(Nter)‐ Hoxa1 Δ11His , pEXP‐FLAG(Nter)‐ Hoxa1 Δ71–199 and pEXP‐FLAG(Nter)‐ Hoxa1 ΔHD have all been described elsewhere. All Hoxa1 expression constructs and mutant derivatives were obtained starting from the mouse cDNA sequence coding for HOXA1 (uniprot number: http://www.uniprot.org/uniprot/P09022).…”
Section: Methodsmentioning
confidence: 99%
“…This allowed pinpointing pathways HOXA1 may take part in either to achieve its molecular functions or to receive regulatory inputs. Among the interacting proteins, several not related to transcription regulation lifted the veil on unexpected nontranscriptional activities of HOXA1, as recently described in the context of the TNFR‐NF‐κB pathway for example .…”
mentioning
confidence: 85%